ANALYZING THE IMPACT OF CONTENT MARKETING ON BRAND AWARENESS - S K Patil; S M Seetalad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the digital age, content marketing has emerged as a critical strategy for enhancing brand awareness. This paper explores the relationship between content marketing and its impact on brand visibility, recognition, and recall. Brand awareness is a crucial factor in consumer decision-making, and content marketing provides a unique opportunity for brands to engage audiences in a non-intrusive, informative, and creative manner. By leveraging various content forms such as blogs, videos, infographics, and social media posts, companies can build an emotional connection with their target audience, thereby fostering trust and loyalty. The paper examines how content marketing works to increase brand awareness through strategic content creation and distribution. It delves into how valuable content, when optimized for search engines, ensures higher visibility, reaching potential customers who may not have previously encountered the brand. Furthermore, content marketing helps to position a brand as an expert or thought leader in its industry, which enhances its credibility and strengthens its identity. Social media platforms amplify this process by facilitating engagement, sharing, and direct communication, significantly extending a brand’s reach. Case studies from notable brands like Amul and Zomato illustrate the effective use of content marketing to elevate brand awareness. Amul’s witty and culturally relevant ads and Zomato’s humorous and timely digital content both show how consistency and relevance play a crucial role in building a recognizable and memorable brand. The paper concludes by highlighting the long-term benefits of content marketing, which, when executed thoughtfully, not only increases brand awareness but also nurtures customer relationships, establishing a foundation for sustainable brand growth in an increasingly competitive marketplace.